INCREASING THE ACCURACY OF THE AVIATION GRAVIMETRIC SYSTEM WITH A TRANSFORMER GRAVIMETER AS A SENSITIVE ELEMENT - Безвесільна, Олена; Гриневич, Марія; Толочко, Тетяна (SWorldJournal, 2023)
The relevance of aviation gravimetric measurements is indisputable. Known aviation gravimeters have both advantages and disadvantages, which are defined in this article. The basis of this work is the highlighting of methods and means of improving the accu